Endoscopic submucosal dissection of endobronchial leiomyoma with a hybrid knife in an adolescent patient: a case report - Wang, Zilin; Hou, Gang (Frontiers in Oncology, 2023)
Endobronchial leiomyomas are uncommon benign tracheobronchial tumors. Bronchoscopic intervention is a safe and effective strategy for patients with contraindications for surgery or refusal to undergo surgery. Endoscopic submucosal dissection (ESD) is widely used to treat early gastrointestinal tumors. The novel hybrid knife is useful during ESD owing to functions of submucosal injections, lesion dissection and hemostasis, and makes ESD more convenient. Here, we report a case of a benign leiomyoma at the orifice of RB7 in an adolescent boy. The diagnosis was confirmed based on bronchoscopic and pathological findings. The patient was successfully treated with combined electrocautery snare and cryoresection, ESD using a hybrid knife and the wound was managed with argon plasma coagulation. The postoperative course was satisfactory, with a good general condition and no severe respiratory symptoms. This is, to our knowledge, the first reported case of ESD using a hybrid knife to treat an endobronchial leiomyoma in an adolescent patient.